Students’ Attitudes and Interests towards ICT and their Achievement in English - Thangam, A. (International Journal of Psychosocial Rehabilitation, 2020)
In the course of recent years, Information and Communication Technologies (ICT) has hugely changed the method for educating and learning. As of late, the Indian Government has worked hard and has, immensely, financed the utilization of ICT gadgets into the instructive part. Be that as it may, its joining disregards students attitudes and interests towards ICT. Without the advancement of these, students attitudes and interests won’t be fruitful nor will be set up to gain new information and to accomplish great brings about the scholastic part. To this end, the current investigation inspected students perspectives towards the incorporation of ICT in training and to recognize the connection between students attitudes, interests and English achievement. To put it in an unexpected way, students with a positive propensity towards the utilization of ICT will prompt good outcomes; they will be bound to be spurred to deal with their own learning, and create the essential aptitudes to become successful students and the contrary remains constant. The discoveries uncover that there is no measurably huge connection among attitudes, interests and a achievement in English.